2013
DOI: 10.1111/odi.12200
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for non‐syndromic oral clefts: a matched case–control study in Hubei Province, China

et al.

Abstract: In our study, we identified that paternal occupational exposure, first-trimester maternal illness, first-trimester maternal bad mood, first-trimester maternal diet of eggs or milk (≥5 meals per week), and first-trimester maternal sexual activities were significantly associated with increased CL/P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
1
6
0
1
Order By: Relevance
“…Consistent with previous studies, a low family income [14], not attending premarital medical examinations [35], family history [1416], maternal occupational hazards exposure [21, 22] and paternal occupational hazards exposure [23] selected as predictors were significantly associated with NSCL/P. According to Krapels et al who examined maternal nutritional factors related to orofacial cleft in Netherlands, increasing intake of vegetable protein can decrease the risk of orofacial cleft [36].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Consistent with previous studies, a low family income [14], not attending premarital medical examinations [35], family history [1416], maternal occupational hazards exposure [21, 22] and paternal occupational hazards exposure [23] selected as predictors were significantly associated with NSCL/P. According to Krapels et al who examined maternal nutritional factors related to orofacial cleft in Netherlands, increasing intake of vegetable protein can decrease the risk of orofacial cleft [36].…”
Section: Discussionsupporting
confidence: 87%
“…Shaw et al found that decreased NSCL/P risk was associated with increased intake of total protein [25]. In China, a case–control study conducted in Hubei Province showed that maternal diet of eggs or milk in first trimmest of pregnancy was significantly associated with a decreased risk of NSCL/P [23]. Similar result was found in our study, showing that milk/soymilk intake in the first trimester of pregnancy was significantly related to NSCL/P.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La ocupación paterna fue reportada en la literatura como factor de riesgo para labio leporino; 26 frecuentemente, granjeros y pintores, por exposición a agroquímicos y a solventes, podrían en forma indirecta exponer a la madre. Otra posible explicación podría ser el estilo de vida materno, con mayor exposición al alcohol y al tabaco 27,28 o a contaminantes ambientales 29 durante el embarazo, por residir en regiones vulnerables a normas de control y seguridad en el manejo de tóxicos.…”
Section: Discussionunclassified
“…The paternal employment modality was reported in the literature as a risk factor for cleft lip 26 given that they are often farmers and painters who are exposed to agrochemicals and solvents, which may result in an indirect exposure for mothers. Other likely explanation may be maternal lifestyle which entails a higher degree of exposure to alcohol and tobacco 27,28 or environmental contaminants 29 during pregnancy because they live in regions subjected to poor regulation regarding toxic agent management and safety.…”
Section: Discussionmentioning
confidence: 99%